Gorée, island of memory - United Nations Educational, Scientific; Cultural Organization; Clémence Cluzel (The UNESCO Courier, 2024)
A symbol of the tragedy engendered by the transatlantic slave trade, the Senegalese island of Gorée has become a flagship destination for memorial tourism, attracting tens of thousands of visitors every year, including many Afro-descendants from abroad.